Advances in cfDNA research for pregnancy-related diseases - Meng, Yimei; Yan, Yu; Yue, Xiaoshan; Li, Yan; Mo, Yanxiang (Frontiers in Cell and Developmental Biology, 2025)
Circulating cell-free DNA (cfDNA) comprises extracellular DNA fragments released into bodily fluids through cellular processes such as apoptosis, necrosis, and active secretion. Alterations in cfDNA concentration, fragmentation patterns, and molecular characteristics under physiological and pathological conditions, including pregnancy-related disorders, have established its value as a minimally invasive biomarker for early disease detection and clinical monitoring. Due to the availability of non- or minimally-invasive and scalable detection platforms with high sensitivity and specificity, cfDNA has emerged as a powerful tool in maternal-fetal medicine. This review provides a comprehensive overview of recent advances in cfDNA research, with an emphasis on its applications in pregnancy-related disorders. We elucidate the underlying biological mechanisms, current diagnostic and prognostic uses, analytical technologies, and the key challenges and future directions for clinical translation.